Effect of distinct environmental actions on the durability of RC slabs strengthened with prestressed CFRP laminate strips - Sena-Cruz, José (2016)
In the context of concrete structures strengthening, the externally bonded reinforcement (EBR) technique is the most widely used strategy. By prestressing the FRP materials attached to the concrete substrate, the ad-vantages of external prestressing and of the EBR technique are combined. The present work investigates the durability of reinforced concrete (RC) slabs strengthened with prestressed CFRP strips according the EBR technique. Two different anchorage systems were studied: (i) the Mechanical Anchorage (MA) and (ii) Gradi-ent Anchorage (GA). The durability of the specimens was evaluated by exposing them to one out of four envi-ronmental conditions, this combined with a sustained load of 1/3 of the ultimate load for a period of 8 months. Finally, the slabs were monotonically tested up to failure by using a four-point bending test configuration. This work presents the general description of the experimental program, the analysis of the main results, as well as retained conclusions.